2008
DOI: 10.1371/journal.pcbi.1000036
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic Signals along Intracellular Membranes May Interconnect Dendritic Spines and Nucleus

Abstract: Synapses on dendritic spines of pyramidal neurons show a remarkable ability to induce phosphorylation of transcription factors at the nuclear level with a short latency, incompatible with a diffusion process from the dendritic spines to the nucleus. To account for these findings, we formulated a novel extension of the classical cable theory by considering the fact that the endoplasmic reticulum (ER) is an effective charge separator, forming an intrinsic compartment that extends from the spine to the nuclear me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Our modeling emphasizes that Ca 2+ waves can have large variability in speed and distance of propagation, which will have major effects on how Ca 2+ is distributed and which targets are hit at what concentrations. However, we note that an entirely different role for ER has been proposed by Shemer et al (2008). Instead of a role for ER in enhancing Ca 2+ waves, they suggested that the ER forms a “cable-within-a-cable” which is electrically active and would provide more rapid distal to proximal communication via electrical signaling comparable to that of the plasma membrane.…”
Section: Discussionmentioning
confidence: 72%
“…Our modeling emphasizes that Ca 2+ waves can have large variability in speed and distance of propagation, which will have major effects on how Ca 2+ is distributed and which targets are hit at what concentrations. However, we note that an entirely different role for ER has been proposed by Shemer et al (2008). Instead of a role for ER in enhancing Ca 2+ waves, they suggested that the ER forms a “cable-within-a-cable” which is electrically active and would provide more rapid distal to proximal communication via electrical signaling comparable to that of the plasma membrane.…”
Section: Discussionmentioning
confidence: 72%
“…Calcium in cytosol comes from the extracellular space, modeled here as an inexhaustible source, and from organelles which are exhaustible. Compared to mitochondria, ER is likely to be a more accessible Ca 2+ source across multiple locations including spines – it spreads diffusely throughout the neuron, foliating at key points to provide additional surface area (Shemer et al, 2008, Berridge, 1998). …”
Section: Discussionmentioning
confidence: 99%
“…3D) (Shemer et al 2008). This proposal is grounded on the basis that, like the plasma membrane, the ER membrane is an effective charge separator and may thus support the generation and propagation of trans-ER depolarizations and hyperpolarizations.…”
Section: The Endoplasmic Reticulum As a Conduit From Synapse To Nucleusmentioning
confidence: 99%
“…An additional means by which synaptic activity could be conveyed to the nucleus involves the passive propagation of electrical potentials along ER membranes to the nuclear envelope ( Fig. 3D) (Shemer et al 2008).…”
Section: Local Ca 2þ Signaling Has Global Functional Consequencesmentioning
confidence: 99%
See 1 more Smart Citation